Genome-wide mapping of DNA double-strand breaks from eukaryotic cell cultures using Break-seq - Joshi, Ishita (STAR Protoc, 2021)
We describe a genome-wide DNA double-strand break (DSB) mapping technique, Break-seq. In this protocol, we provide step-by-step instructions for cell embedment in agarose, in-gel DSB labeling and subsequent capture, followed by standard Illumina library construction and sequencing. We also provide the framework for sequence data processing and DSB peak identification. Finally, we present a custom-designed 3D-printed device for processing agarose-embedded DNA samples. The protocol is applicable to Saccharomyces cerevisiae, as well as mammalian suspension, adherent, and 3D organoid cell cultures. For complete details on the use and execution of this protocol, please refer to Hoffman et al. (2015) and Chakraborty et al. (2020).